Spontaneous Coronary Artery Dissection in Pregnancy Requiring Emergency Caesarean Delivery Followed by Coronary Artery Bypass Grafting. Issue 2 (March 2013) - Weinberg, L.; Ong, M.; Tan, C. O.; Mcdonnell, N. J.; Lo, C.; Chiam, E.
Spontaneous coronary artery dissection is a rare and often fatal condition of pregnancy. The long-term morbidity is unknown, but a small cohort of patients develop severe ventricular dysfunction as a consequence. We describe a 37-week gestation parturient who presented with cardiogenic shock secondary to spontaneous left main coronary artery dissection. Despite rapid diagnosis, stabilisation with an intra-aortic balloon pump and prompt transfer to a tertiary centre for emergency caesarean delivery and coronary artery bypass grafting, the patient developed a severe postoperative dilated ischaemic cardiomyopathy. There is little information about the long-term outcomes and the specific anaesthesia management of combined emergency caesarean delivery and cardiac surgery in pregnancy for spontaneous coronary artery dissection. Therefore, we outline our multidisciplinary management of this critically ill pregnant woman.